FUNGSI TATA RUANG DALAM MENJAGA KELESTARIAN LINGKUNGAN HIDUP KOTA GORONTALO - SuwitnoY Imran (Faculty of Law, Universitas Jenderal Soedirman, 2013)
The result of this research showed that the spatial arrangement of the function in preserving the environment is experiencing a variety of problems; First, the conflict between sectors and across regions. Second, environment degradation due to the spatial deviations among land, sea and air. Thind, support for the development of the region is not optimal, as indicated by the lack of policy support for the development of strategic areas of national and local goverments. Therefore, it needs a commitment from Gorontalo city government to address these problems through or local lawch which regulate the spatial function of Gorontalo City. Keywords : spatial, environment, environmental law